A Business Model for Circular Bioeconomy: Edible Mushroom Production and Its Alignment with the Sustainable Development Goals (SDGs) - Viriato, Viviany [UNESP]; Carvalho, Silvia Angélica Domingues de [UNESP]; Santoro, Bruno de Lima; Bonfim, Filipe Pereira Giardini [UNESP] (MDPI, 2024)
Agricultural wastes (AWs) generated from farming practices pose environmental threats if not properly disposed of or recycled through biological processes. Mushroom production presents a sustainable solution by converting AWs into highly nutritious food while mitigating environmental pollution. However, there is a lack of comprehensive frameworks to assist farmers and businesses in visually understanding the essential elements of a circular bioeconomy, such as mushroom production’s potential interconnections and impacts on value creation. This study theoretically elaborates on a framework using the Business Model Canvas to structure mushroom production across the following key business areas: customers, supply chains, infrastructure, and economic viability. We discuss these aspects within the context of recent studies. In addition to guiding farmers and businesses, we align mushroom production with Sustainable Development Goals (SDGs) within the supply chain, underscoring the importance of developing business models to foster the growth of circular economies and sustainability.
Keywords: agricultural wastes recycling; business model; circular bioeconomy; mushroom cultivation; Sustainable Development Goals